IMMUNOBIOLOGICAL CONTROL SYSTEM AND IMMUNOPATHOLOGICAL SYNDROMES - P.F. Litvitsky ("Paediatrician" Publishers LLC, 2007)
This publication is the first one in a series of brief lectures dedicated to the characteristics of the immunobiological control system, aetiology and pathogenesis, which most frequently occur in the medical practices of the immunepathological syndromes: immunodeficiencies, allergic reactions, pathologic tolerance, graft-versus-host disease, immune autoaggression syndromes. Key words: immunobiological control system, immunodeficiency, allergic reactions, pathologic tolerance, graft versus host diseases, immune autoaggression syndromes.